KONTRIBUSI LATIHAN HORIZONTAL SWING DAN TWISTING TRUNK CURL TERHADAP HASIL PUSH PADA ATLET PUTRI TELADAN HOCKEY CLUB BATU BARA TAHUN 2021 - Rizki Fauzi; Rahma Dewi (Journal Physical Health Recreation (JPHR), 2021)
This study aims to determine the contribution of horizontal swing and twisting trunk curl exercises to the improvement of push hockey results in female athletes of the Batu Bara Exemplary Hockey Club in 2021. The research method used in this research is the experimental method, the sample used in this study is 12 people. The research was conducted on May 24, 2021 until July 3, 2021, the statistical calculations used in this study are; requirements analysis test, normality test, homogeneity test and regression significance test. The first analysis is that the horizontal swing exercise provides a significant contribution to increasing the results of push hockey in female athletes of the Batu Bara Exemplary Hockey Club in 2021, based on the calculation results Fcount = 18.990 and Ftable(0.05;1/10) = 4.96 so Fcount > Ftable it can be concluded that the regression equation model is significant about 65.5%. Analysis of the second hypothesis, namely, twisting trunk curl exercise contributes to increasing push hockey results in female athletes of the Batu Bara Exemplary Hockey Club in 2021, based on the calculation results Fcount = 21.670 and Ftable(0.05;1/10) = 4.96 so Fcount > Ftable it can be concluded that the regression equation model is significant about 65.3%. Analysis of the third hypothesis, namely, horizontal swing and twisting trunk curl exercises jointly contributed significantly to the improvement of push hockey results in female athletes at the Batu Bara Exemplary Hockey Club in 2021. Approximately 74.2% of horizontal swing and twisting trunk curl exercises contributed to push hockey results for female athletes of the Batu Bara Exemplary Hockey Club in 2021. From hypothesis testing it can be concluded that; there is a significant contribution from the horizontal swing and twisting trunk curl exercises, there is a significant contribution jointly from both forms of exercise to the improvement of push hockey results in female athletes of the Batu Bara Exemplary Hockey Club in 2021.